Implementasi Internet of Things untuk Irigasi Media Tanam Pembenihan Kentang dan Pengembangan Sumber Daya Manusia Mitra Tunas Muda Farm - Muhamad Cahyo Ardi Prabowo; Mujahidin, Irfan; Artha Rochmanto , Raditya; Pinandhito , Kenneth; Rosita Cendrasari, Erie; Flaurecita Gadis Bermana, Cello; Fernanda Mardiansyah , Adriel (Politeknik Negeri Jember, 2025)
The Internet of Things (IoT) is one of the technological advances that can integrate various devices in one internet communication network, including in the agricultural sector. Tunas Muda Farm is an agricultural business that focuses on potato seeding. In fact, partners experience challenges in managing the potato seed production process with conventional planting media in the screen house. As a result, there is an inequality in quality, production output does not increase, and operational costs are high. The purpose of this program is service at Tunas Muda Farm partners in Wonosobo Regency with 2 activities, namely (i) the implementation of appropriate technology for IoT irrigation systems that combine fog irrigation techniques and drip irrigation integrated sensors and websites, (ii) appropriate technology training to increase the knowledge of human resources in the farmer partner environment. Monitoring parameters for plant seedling care include temperature and humidity of the screen house, real-time humidity of the planting medium via smartphone. The impact of this program helps farmers through the application of technology and strengthens human resources in partner environments.